Designing CCTV Working Optimization System as Room Security Using Passive Infrared (PIR) Sensor Based on AT89S52 Microcontroller - Dwijaputra, IGN Agung; Satriya Wibawa, I Made; Wendri, Nyoman (BULETIN FISIKA; Vol 19 No 2 (2018): BULETIN FISIKA, 2018)
A CCTV optimization system has been designed using PIR (passive infrared) sensor based on AT89S52 microcontroller. This device consists of several series of sensor circuit, AT89S52 microcontroller minimum system, stepper motor driver circuit, push-on circuit and alarm circuit. The working system of the room safety device is when the PIR (passive infrared) sensor detects the movement of the object, then the output of the sensor is forwarded to the microcontroller, the microcontroller will process and convey to the driver circuit to drive the stepper motors that moves the CCTV. The push-on circuit is connected to the microcontroller port for controlling the movement of the stepper motor so it won’t rotate beyond 180 degrees, and for the safety of the room, an alarm circuit is connected to the microcontroller port as an alarming sound generator.